Maintenance Performance of Malaysia's Automotive Sector: A Case Study - Muhamad Arifpin, Mansor; L. H., Shah; Hazami, Che Hussain (2012)
Today, maintenance is considered as an indispensable part of the business process. Efficiency and effectiveness of the maintenance function will affect the performance of the production system and the capability of the machine to produce quality products. One of the excellent tools for the benchmarking process is Data Envelopment Analysis (DEA). DEA has been widely applied to perform efficiency analysis in many sectors. In this research, we apply DEA to measure maintenance performance for one of the major automotive manufacturer in Malaysia. The assessment was performed in two trials to demonstrate the importance of identifying the inputs and outputs and to determine the effect of certain input. The assessment was conducted based on general model for maintenance with the appropriate inputs (cause) are man, machine, money, training, and time, or â3M2Tâ and the outputs (affect) are production, quality, cost, delivery, safety, morale, and time, or âPQCDSMTâ.